Frequency of Recurrent Laryngeal Nerve Palsy after Thyroidectomy at Sheikh Khalifa Bin Zaid Hospital Rawlakot Azad Kashmir (Medical Forum Monthly, 2024)
Objectives: The objective of the study was to determine the frequency of post thyroidectomy RLN palsy and to adopt measures to reduce the frequency of RLN palsy after thyroidectomy.Study Design: Descriptive studyPlace and Duration of Study: This study was carried out at General Surgery Department, Sheikh Khalifa Bin Zaid Hospital Rawlakot Azad Kashmir from 16.11.2012 to 16.11.2014Materials and Methods: Total of 80 patients of goiter undergoing thyroidectomy were admitted through outpatient department. All patients underwent thorough clinical examination and investigations. They were informed of the benefits and risks associated with surgery and written informed consent was obtained. All information was recorded on performa. Vocal cord status was assessed pre and postoperatively by indirect laryngoscopy. Size of thyroid gland was measured before operation in all the patients and weight of thyroid tissue removed during operation was also assessed. 03 patients were excluded from the study as they were already having hoarseness of voice.29 were subjected to subtotal thyroidectomy, 30 to total thyroidectomy, and 21 to hemi-thyroidectomy randomly. All were followed up for RLN palsy for 03 months. According to our objective, no test of significance was applicable. However, descriptive statistics including mean, standard deviation was used by using Microsoft statistical package for social sciences “SPSS Version 10.”Results: The age range of the patients undergoing thyroidectomy was 20-68 years with an average age of 44. Total mortality rate was 0%. Transient hoarseness of voice was present in 01(1.2%) which improved spontaneously with time and permanent hoarseness in 0% patients. No patient was lost at any point.Conclusion: Frequency of RLN palsy can be reduced by careful identification of recurrent laryngeal nerve by various methods per-operatively.